Comparative Investigation of Vortex and Direct Plasma Discharge for Treating Titanium Surface - Hyun-Jeong Jeon; Subin Seo; Ara Jung; Kyeong-mok Kang; Jeonghoon Lee; Bomi Gweon; Youbong Lim (Biomimetics)
Numerous studies have investigated the surface treatment of implants using various types of plasma, including atmospheric pressure plasma and vacuum plasma, to remove impurities and increase surface energy, thereby enhancing osseointegration. Most previous studies have focused on generating plasma directly on the implant surface by using the implant as an electrode for plasma discharge. However, plasmas generated under atmospheric and moderate vacuum conditions often have a limited plasma volume, meaning the shape of the electrodes significantly influences the local electric field characteristics, which in turn affects plasma behavior. Consequently, to ensure consistent performance across implants of different sizes and shapes, it is essential to develop a plasma source with discharge characteristics that are unaffected by the treatment target, ensuring uniform exposure. To address this challenge, we developed a novel plasma source, termed “vortex plasma”, which generates uniform plasma using a magnetic field within a controlled space. We then compared the surface treatment efficiency of the vortex plasma to that of conventional direct plasma discharge by evaluating hydrophilicity, surface chemistry, and surface morphology. In addition, to assess the biological outcomes, we examined osteoblast cell activity on both the vortex and direct plasma-treated surfaces. Our results demonstrate that vortex plasma improved hydrophilicity, reduced carbon content, and enhanced osteoblast adhesion and activity to a level comparable to direct plasma, all while maintaining the physical surface structure and morphology.